Risk Factors of Stunting in Children Under Two Years of Age in Donggala District Central of Sulawesi - Fahmi Hafid; Nasrul Nasrul; A. Bungawati; Kadar Ramadhan (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Stunting is a critical public health issue, with multifactorial risk factors that can include a child's gender, birth length, low birth weight, and unhealthy snack consumption. The aim of this research is to analyze the risk factors for stunting in toddlers in Donggala District. This study employed an analytical approach with a cross-sectional design. The research was conducted in Donggala District, with the target population being children aged 6-23 months. A sample of 397 toddlers was obtained through cluster simple random sampling. The respondents were mothers of the toddlers. Data collection took place in August 2023. The independent variables included in the study were the characteristics of mothers and households, child characteristics, disease history, healthcare access, and dietary intake. The dependent variable was stunting status. Stunting data were obtained by measuring the child's length using Length Board Measuring (LMB) and determining age by reading the birth certificate or the child's KIA book. Other data were collected through the Kobocollect questionnaire. Data analysis was conducted using SPSS version 22.00, with Z-Score values based on WHO-Antro 2005 standards. Multivariate analysis employed backward logistic regression. The research results indicated that significant factors contributing to the risk of stunting in toddlers in Donggala District included the child's gender, birth length, low birth weight, and consumption of unhealthy snacks. Birth length (AOR=1.8, 95% CI: 1.1-3.1), child gender (AOR=1.7, 95% CI: 1.0-2.7), low birth weight (AOR=2.3, 95% CI: 1.0-5.2), and unhealthy snack consumption (e.g., chips, cheese balls) (AOR=2.0, 95% CI: 1.0-3.8) were all significant factors. Policies addressing aspects such as nutrition, maternal and child healthcare services, supervision of unhealthy snacks, and monitoring and evaluation would help reduce the risk of stunting and improve the quality of life for children in Donggala District